al-Muqārabah bil-Ihtimām wal-Mawāhib lii Tarqiyati Mahārat al-Qirā’ah bil-Lughah al- ‘Arabiyyah lii Tullāb al-Ma‘had Wali Songo Lampung al-Wustha - Siti Nur Azizah; Nailul Izzah; Muhammad Syaifullah (Al Maghazi : Arabic Language in Higher Education, 2025)
Arabic language learning, especially reading skills, often faces challenges such as low motivation and limited student engagement. Traditional approaches tend to focus on cognitive aspects while neglecting students’ interests and talents, which are important for effective learning. In Islamic boarding schools, where Arabic is essential for understanding religious texts, improving reading skills requires innovative and student-centered strategies. This study aims to examine the effectiveness of an interest- and talent-based approach in improving Arabic reading skills among students of Wali Songo Islamic Boarding School, Central Lampung. The study is grounded in the assumption that accommodating students’ interests and talents can enhance their learning motivation and generate a positive impact on the development of their language competencies, particularly reading skills. A qualitative method was employed through participant observation, interviews, and document analysis to explore the forms of program implementation and to analyze its influence on the development of students’ reading abilities. The findings reveal that the approach is implemented through various extracurricular activities, such as Arabic speech, drama, and book discussions, which are systematically integrated with classroom instruction. These activities contribute significantly to the improvement of students’ reading skills in terms of literal comprehension, inferential comprehension, and reading fluency, including accurate pronunciation and smooth delivery. Furthermore, the results indicate that engaging students in activities aligned with their interests strengthens their active participation and fosters a stronger connection with the Arabic language. In conclusion, the interest- and talent-based approach represents an effective educational strategy for enhancing Arabic reading skills, as it provides a motivating learning environment that integrates cognitive, skill-based, and affective dimensions, while making the Arabic language more relevant to students’ real-life experiences and interests.